Short-term responses to flooding stress of three Prunus rootstocks - Ziegler, Victor H. (2017)
In fruit trees, flooding stress can affect plant survival and growth, and tolerance to root anoxia is determined by rootstock characteristics. Similarly to almond, peach trees are also among the Prunus species proving most susceptible to root anoxia in flooded soils. The aim of our study was to investigate the short-term responses to flooding of different Prunus rootstocks, in terms of growth and development and physiological variables. Flood treatments were continuously applied for 6 days to myrobalan plum Sansavini 2/5 (Mr. S. 2/5), Monegro and Nemared peach rootstocks. Trees that were not exposed to flooding served as controls. Physiological and growth variables were evaluated. Flooding negatively affected net photosynthesis (Pn), leaf conductance (gs) and water potential (Ѱw) in Monegro and Nemared but not in Mr. S. 2/5 rootstock. However, flooding treatments did not affect the intercellular concentration of CO2 (Ci) in any of the rootstocks. We propose that the lack of alterations in Ci indicates that the processes related to photosynthetic metabolism are affected simultaneously with stomatal closure. Flooding only reduced the leaf growth of Monegro and Nemared rootstocks. The Mr. S. 2/5 rootstock had the highest constitutive root porosity, which increased its tolerance to flooding compared to the other rootstocks. The differences in the responses to flooding of various rootstocks should be considered in production settings where it is not possible to properly control irrigation to prevent short periods of flooding or in soils that do not drain irrigation or rain water quickly.